2018
DOI: 10.3389/fphar.2018.00751
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic and Antiepileptic Properties of the Aqueous Extract of Cissus quadrangularis (Vitaceae) in Mice Pilocarpine Model of Epilepsy

Abstract: Cissus quadrangularis (C. quadrangularis) is a plant of the Vitaceae family known for its anticonvulsant effects in traditional medicine. The objective of this study was to elucidate the anxiolytic and antiepileptic effects of aqueous extract of C. quadrangularis. The mice were divided into different groups and treated for seven consecutive days as follows: a negative control group that received distilled water, po, four test groups that received four doses of the plant (37.22, 93.05, 186.11, and 372.21 mg/kg,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 63 publications
2
27
0
Order By: Relevance
“…Cissus spp. have antioxidant functions in various disease models [2,[30][31][32][33][34][35]. In the present study, we validated the cellular toxicity of CVE in HT22 hippocampal cells based on the cell viability, ROS formation, and DNA fragmentation.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Cissus spp. have antioxidant functions in various disease models [2,[30][31][32][33][34][35]. In the present study, we validated the cellular toxicity of CVE in HT22 hippocampal cells based on the cell viability, ROS formation, and DNA fragmentation.…”
Section: Discussionmentioning
confidence: 63%
“…In addition, microglial activation induced by ischemia was markedly decreased by treatment with 300 mg/kg, but not 30 mg/kg, CVE 4 d after ischemia. Several studies have demonstrated that treatment with C. quadrangularis mitigates lipid peroxidation in ovariectomized bone tissue [33], pilocarpine-induced epileptic hippocampus [34], and nicotinamide and streptozotocin-induced diabetic liver [32]. C. quadrangularis extract inhibits IL-1β induced inflammatory responses in chondrocytes [44].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, oral administration of Lippia multiflora aqueous extracts increased the percentage of entries into and time spent in the open arms of the elevated plus maze, while it decreased the percentage of time spent on the closed arms. An increase in the percentage of entries into and time spent in the open arms refers to a decrease in anxiety [28,29] and a decrease in these behavioural parameters in closed arms reflects a reduction in stress [17,19,28]. These results indicate that Lippia multiflora aqueous extracts has anxiolytic-like activity.…”
Section: Discussionmentioning
confidence: 92%
“…Extracts of C. quadrangularis signi icantly and dose-dependently increased the latency to clonic and generalized tonic-clonic seizures and decreased the number and duration of seizures. Anticonvulsant activities of the plant are accompanied by its anxiolytics effects which are supported by its antioxidant properties and mediated [33]. C. quadrangularis being rich in antioxidants such as vitamin C and lavonoids was studied for its effect on the antioxidant system of femur in ovariectomized rats by Muthusami, et al [34].…”
Section: Anti-oxidant Activitymentioning
confidence: 99%